2020
DOI: 10.34172/aim.2020.116
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Derived Conditioned Medium in Pulmonary Fibrosis: A Systematic Review and Meta-analysis

Abstract: Background: A definitive conclusion on the efficacy of mesenchymal stromal cells-derived conditioned medium (MSCs-CM) in pulmonary fibrosis has not yet been reached. Therefore, the present meta-analysis intends to investigate the efficacy of MSCs-CM administration on improvement of pulmonary fibrosis. Methods: An extensive search was performed on the Medline, Embase, Scopus and Web of Science databases by the end of August 2019. Outcomes in the present study included pulmonary fibrosis score, lung collagen dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…In addition, using an animal experimental model of IPF, we found that our CM reduced lung tissue production of pro-inflammatory cytokines, it had an anti-fibrotic effect capable of inhibiting inflammatory and fibrotic responses in the lung, ameliorating fibrosis, and it also was safe for the animals used [ 56 ]. Overall, the CM we used seems to exert immunomodulatory properties, it was safe for the animal model, and as mentioned earlier AD-MSCs exert similar antifibrotic properties with CM of different stem cell origin [ 55 ], which makes it a plausible candidate for further development towards a treatment for IPF. There is evidence that the CM of adipose-derived-MSCs interact with NK cells, monocytes, macrophages, and effector and regulatory T cells to shift their pro-inflammatory T helper type 1 (Th1) cytokine secretion profile to an anti-inflammatory T helper type 2 (Th2) cytokine profile [ 64 ].…”
Section: Conditioned Medium In Pulmonary Fibrosismentioning
confidence: 82%
See 3 more Smart Citations
“…In addition, using an animal experimental model of IPF, we found that our CM reduced lung tissue production of pro-inflammatory cytokines, it had an anti-fibrotic effect capable of inhibiting inflammatory and fibrotic responses in the lung, ameliorating fibrosis, and it also was safe for the animals used [ 56 ]. Overall, the CM we used seems to exert immunomodulatory properties, it was safe for the animal model, and as mentioned earlier AD-MSCs exert similar antifibrotic properties with CM of different stem cell origin [ 55 ], which makes it a plausible candidate for further development towards a treatment for IPF. There is evidence that the CM of adipose-derived-MSCs interact with NK cells, monocytes, macrophages, and effector and regulatory T cells to shift their pro-inflammatory T helper type 1 (Th1) cytokine secretion profile to an anti-inflammatory T helper type 2 (Th2) cytokine profile [ 64 ].…”
Section: Conditioned Medium In Pulmonary Fibrosismentioning
confidence: 82%
“…Administration of MSCs-CM exerts all the beneficial effects derived from the paracrine action and secretome production from stem cell transplants, without the side effects of stem cell transplants [ 4 ]. Thus, the use of CM has been proposed as a potentially effective therapeutic strategy for the treatment of pulmonary fibrosis, and MSCs-CM has been used in experimental and clinical studies [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Conditioned Medium In Pulmonary Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic strategy is mainly based on the use of corticosteroids, hydroxychloroquine, azithromycin, and supportive care; however, the efficacy is of these methods is variable. The role of MSCs as a state-of-the-art treatment has been proposed in clinical and preclinical studies [ 4 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%